OPTIMALISASI TUMBUH KEMBANG BAYI MELALUI EDUKASI, TERAPI PIJAT BAYI (BABY MASSAGE) DAN SENAM BAYI (BABY GYM) DI KLINIK BERSALIN KOTA MEDAN DAN KABUPATEN DELI SERDANG TAHUN 2018 - Br Karo, Evi Indriani; Kaban, Febrina Oktavinola (Jurnal Riset Hesti Medan, 2019)
Every parent expects their children to grow and develop optimally, so that they can become qualified and resilient human resources. Achieving optimal growth and development is the result of interaction with various factors, one of them is stimulation. Massage (stimulation touch) that is done correctly and regularly will greatly benefit the baby's growth. Maternity clinic is one of the health facilities that provide services to mothers, babies and toddlers including monitoring baby's growth. The community service activities were held at Shanty clinic located in Sungai Berombang Village, Medan Barat sub-district, Medan, and Pratama Clinic Fitri Asih, which was in Patumbak Deli Serdang. Based on the situation analysis of the two partners in the development of their services, they still experience various problems, namely: very low knowledge of the community, especially the mothers of infants and toddlers regarding efforts to optimize baby growth with baby massage and baby gymnastics, lack of partner skills and expertise to do baby massage and limited facilities and infrastructure at both partners. The solutions offered are education and training on infant massage and baby gymnastics and help complete the facilities and infrastructure needed by partners according to their abilities. This activity began in mid-January 2018 and was held on April 17, 2018 at Fitri Asih Clinic and May 30, 2018 at Shanty Midwife Clinic. This activity was attended by 40 mothers and their babies. The results of the activity evaluation showed that there was an increase in mother's knowledge so that they were eager to do gymnastic movements according to their baby's age. There was an increase in maternal skills so they were more confident in doing massage on their babies. Mentoring and guidance for partners has a positive impact to maximize clinical services in optimizing baby's growth.Keywords: Education, Training, Baby Massage, Infant Gymnastics